Perancangan Typeface Alfabet Memanfaatkan Aksara Incung Sebagai Sumber Ide Gagasan - Ria Sapitri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2020)
Typeface is a "appearance" that forms the characteristics of a collection of letters so that it distinguishes it from other types of letters. Typeface artwork is considered capable of providing new inspiration to introduce one of Kerinci's local wisdoms, the incung script. Visually, incung script has the beauty of a form of writing style that is slanted, curved and broken beheaded. The basic shape of each incung alphabet is formed by sharp lines so that it seems stiff and classic. Based on the description above, the author's interest arises to introduce or familiarize the incung script back to the younger generation as the Kerinci people's identity in the form of digital-based typeface novelty.